A rationally designed 2C inhibitor prevents enterovirus D68-infected mice from developing paralysis - Kan Li; Michael J. Rudy; Yanmei Hu; Haozhou Tan; George Lambrinidis; Xiangmeng Wu; Kyriakos Georgiou; Bin Tan; Joshua Frost; Courtney Wilson; Penny Clarke; Antonios Kolocouris; et al. (Nature Communications)
Abstract Enterovirus D68 (EV-D68) is a respiratory virus that often causes mild to moderate respiratory illnesses and, in severe cases, can lead to paralysis and rarely death, mainly in children. There is currently no vaccine or antiviral for EV-D68. Here, we report the rational design of viral 2 C inhibitors for treating EV-D68 infection-induced paralysis in a neonatal mouse model. Viral 2 C protein is a multi-functional protein vital for viral replication. Structure-based drug design identifies Jun6504 showing potent and broad-spectrum antiviral activity against multiple strains of EV-D68, EV-A71, and CVB3, as well as favorable in vitro and in vivo pharmacokinetic properties. In a neonatal mouse model of EV-D68 infection, Jun6504 significantly improves paralysis score and weight gain when administered immediately or 24 hours post-infection. Jun6504 also reduces viral titers in the spinal cord and the infected quadriceps muscle. Collectively, Jun6504 represents a promising candidate for further development as an EV-D68 antiviral.